PENERAPAN STANDARISASI HOSPITALITY DI DESA WISATA PENTINGSARI - , T.SAIFUDDIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
good service is a key to obtaining customersâ loyalty. When the service given by a company, in this case a tourism village, is not optimal and not as expected by its customers, the company will be difficult to develop and will be defeated by other companies which can offer better services. So, the most important aspect that must be highly maintained by a company manager is the service given to consumers. Service providing optimality can be measured by looking at the impression taken by customers at the time they were done using the services provided by the company. By looking at those facts, author wanted to know the standardization level of services provided by the services corporate manager. Author examines the Hospitality Standardization Implementation in Pentingsari Tourism Village by researching service optimality given to guests at the village. Another goal the author examined in this research is supporting and restricting factors of hospitality standardization implementation in Desa Wisata Pentingsari, so with this study it is expected the service in Pentingsari tourism village can be improved to get the guests loyalty. In this research the author uses qualitative analysis, by describing the solution of the problems based on the data author obtained through observation, participatory, and documentation so that author can formulize the problems to conclude this research. The results of this final project writing, the author could find out about hospitality standardization implemented in Desa Wisata Pentingsari to give maximum satisfaction to the guests and the supporting and restricting factors in providing service to guests. Those are, the Javanese hospitality used as the basic foundation in providing service to guests is a supporting factor in the hospitality standardization implementation. As the restricting factor, is the inexistence of complaints service and also the lack of knowledge about Pentingsari tourism village itself by the tourist guides. Still, these restricting factors can be resolved with the Javanese hospitality as the basic foundation.